Microstructural Parcellation of the Human Cerebral Cortex – From Brodmann's Post-Mortem Map to in vivo Mapping with High-Field Magnetic Resonance Imaging - Geyer, Stefan; Weiss, Marcel; Reimann, Katja; Lohmann, Gabriele; Turner, Robert (Frontiers in Human Neuroscience, 2011)
The year 2009 marked the 100th anniversary of the publication of the famous brain map of Korbinian Brodmann. Although a "classic" guide to microanatomical parcellation of the cerebral cortex, it is – from today's state-of-the-art neuroimaging perspective – problematic to use Brodmann's map as a structural guide to functional units in the cortex. In this article we discuss some of the reasons, especially the problematic compatibility of the "post-mortem world" of microstructural brain maps with the "in vivo world" of neuroimaging. We conclude with some prospects for the future of in vivo structural brain mapping: a new approach which has the enormous potential to make direct correlations between microstructure and function in living human brains: "in vivo Brodmann mapping" with high-field magnetic resonance imaging.